First evidence of independent pseudogenization of toll-like receptor 5 in passerine birds - Bainová, Hana; Králová, Tereza; Bryjová, Anna; Albrecht, Tomáš; Bryja, Josef; Vinkler, Michal (Developmental and comparative immunology, 2014)
Toll-like receptor 5 (TLR5) is a Pattern-recognition receptor responsible for microbial flagellin detection in vertebrates and, hence, recognition of potentially pathogenic bacteria. Herein, we report emergence of TLR5 pseudogene in several phylogenetic lineages of passerine birds (Aves: Passeriformes). Out of 47 species examined in this study 18 possessed a TLR5 pseudogene. Phylogenetic analysis together with the type of mutation responsible for pseudogenization indicate that TLR5 pseudogene emerged at least seven times independently in passerines. Lack of any functional copy of the gene has been verified based on TLR5 mRNA blood expression in four species representing the four main passerine lineages possessing the TLR5 pseudogene. Our results suggest that the non-functional TLR5 variant is fixed in those lineages or, at least, that individuals homozygote in the TLR5 pseudogene are frequent in the investigated species. Further research is needed to assess the impact of the TLR5 loss on immunological performance in birds.
Keywords: exprese genu; toll-like receptor 5; Gene Expression; Toll-Like Receptor 5; vrabcovití; ptačí proteiny; fylogeneze; Phylogeny; Sparrows; Avian Proteins; molekulární evoluce; Evolution, Molecular; Toll-like receptor 5; Expression; Innate immunity; Pseudogene; Birds; Animals; Flagellin; zvířata; pseudogeny; Pseudogenes